Equipping Vocational College Students with Statistical Literacy: A Demonstrative Workshop on Statistical Tests and Procedures to Improve Rigor in Students’ Final Year Project Data Analysis - Idek, Sirhajwan; Raymond, Rowdella; Mislan, Sufi Abidin; Akul, Yushahfira; Damit, Dayang Siti Khatijah Awang; Lang, Lumang Anak (Future Science / FSH-PH Publications, 2025)
The purpose of this research project was to learn about the experience that final year students of Keningau Vocational College Statistical had in a physical workshop on statistical methods as well as their need to learn more about statistics and the software used to process them in helping them with their quantitative data analysis in their final year project development. Past final year projects only presented raw data which the students used to draw conclusions from without using any detailed statistical methods to identify trends and patterns. Therefore, their findings remained superficial, generic and less meaningful which made it harder for their findings to be deemed as valid, reliable and convincing. Hence, a statistical test and procedure workshop which featured live demonstration of a predetermined set of data was con-ducted on all final year students at the college. The software used was Statistical Product and Service Solutions (SPSS). The live demonstration was followed by the students’ attempt in emulate the procedure shown to them in order to help them understand it better. They were required to purchase and install the software prior to the workshop. The findings revealed that the students felt that their understanding of the topic im-proved significant after the workshop and they deemed the software to be useful in their data analysis but found it challenging to use. The stu-dents’ responses also implied that the students felt the hands-on and interactive instruction with guided practice could help them become more adept at using the software and gain better understanding of the topic. The findings signified the need to explore several instruction and learning methods as well as materials that may significantly improve the delivery approach. The findings also revealed a compelling need to fully integrate statistical tests and procedures into the vocational col-lege curriculum.